2013
DOI: 10.1088/0004-637x/776/1/30
|View full text |Cite
|
Sign up to set email alerts
|

CIRCULARITY OF THEINTERSTELLAR BOUNDARY EXPLORERRIBBON OF ENHANCED ENERGETIC NEUTRAL ATOM (ENA) FLUX

Abstract: As a sharp feature in the sky, the ribbon of enhanced energetic neutral atom (ENA) flux observed by the Interstellar Boundary Explorer (IBEX) mission is a key signature for understanding the interaction of the heliosphere and the interstellar medium through which we are moving. Over five nominal IBEX energy passbands (0.7, 1.1, 1.7, 2.7, and 4.3 keV), the ribbon is extraordinarily circular, with a peak location centered at ecliptic (λ RC , β RC ) = (219.• 2 ± 1.• 3, 39.• 9 ± 2.• 3) and a half cone angle of φ C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
155
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 132 publications
(173 citation statements)
references
References 38 publications
16
155
2
Order By: Relevance
“…2 we show an example of the simulated ribbon flux rotated to a common ribbon-centered frame. In this frame we derive key geometrical properties, such as the ribbon center, radius, eccentricity, and rotation angle, similar to the analysis of Funsten et al (2013).…”
Section: Circularity Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2 we show an example of the simulated ribbon flux rotated to a common ribbon-centered frame. In this frame we derive key geometrical properties, such as the ribbon center, radius, eccentricity, and rotation angle, similar to the analysis of Funsten et al (2013).…”
Section: Circularity Resultsmentioning
confidence: 99%
“…This discrepancy between the simulation and observation is likely due to our use of uniform SW boundary conditions. Also, Funsten et al (2013) found that there is a significant dependence of the IBEX ribbon rotation angle on ENA energy. If the semi-major axis is related (but perpendicular) to the energy-dependent symmetry axis of the IBEX ribbon found by Funsten et al (2015), and the unimodal/bimodal symmetry of the IBEX ribbon as a function of ENA energy is affected by the asymmetric SW, then it is reasonable to suggest that the rotation angle of the IBEX ribbon is also affected by the latitudinal asymmetry of the SW. Non-ribbon ENA emission features may lie within the region scribed by the ribbon and may A31, page 10 of 13 also contribute to both non-circularity and asymmetry at different energies (Funsten et al 2015).…”
Section: Comparing Simulated and Ibex Ribbon Geometrymentioning
confidence: 90%
See 2 more Smart Citations
“…In Figure 4, we plot in ecliptic coordinates the ISM field direction inferred from the IBEX ribbon center (Funsten et al 2013) and the upwind ISM flow direction from WMW15, with the connecting line indicating the path along a great Funsten et al 2013), the upwind direction of the ISM He flow (green box; WMW15), the upwind direction of the H flow in the solar system (light blue box; Lallement et al 2005Lallement et al , 2010, the IBEX-derived upwind direction of the secondary He flow (solid blue box; Kubiak et al 2016), and the Ulysses-derived upwind direction of the secondary He flow (dotted blue box; this paper). The boxes indicate the quoted uncertainties in the directions.…”
Section: Deflection From the Ism Flow Directionmentioning
confidence: 99%